2018
DOI: 10.3390/f9070389
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Deforestation in Rainforests Using Satellite Data: A Pilot Study from Kalimantan, Indonesia

Abstract: Monitoring large forest areas is presently feasible with satellite remote sensing as opposed to time-consuming and expensive ground surveys as alternative. This study evaluated, for the first time, the potential of using freely available medium resolution (30 m) Landsat time series data for deforestation monitoring in tropical rainforests of Kalimantan, Indonesia, at sub-annual time scales. A simple, generic, data-driven algorithm for deforestation detection based on a consecutive anomalies criterion was propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…The four commonly used broadband vegetation indices (VI) were initially examined, namely the normalized difference vegetation index (NDVI) [7], enhanced vegetation index (EVI) [8], normalized difference moisture index (NDMI), also known as normalized difference water index [9] and normalized burn ratio (NBR) [10]. It was observed that NDMI shows high sensitivity (most clear signal) in response to deforestation events in the study area, with signal change magnitude most visibly larger than ephemeral noise [11] NDMI was calculated as follows:…”
Section: Pre-processing Dataset and Literature Reviewmentioning
confidence: 99%
“…The four commonly used broadband vegetation indices (VI) were initially examined, namely the normalized difference vegetation index (NDVI) [7], enhanced vegetation index (EVI) [8], normalized difference moisture index (NDMI), also known as normalized difference water index [9] and normalized burn ratio (NBR) [10]. It was observed that NDMI shows high sensitivity (most clear signal) in response to deforestation events in the study area, with signal change magnitude most visibly larger than ephemeral noise [11] NDMI was calculated as follows:…”
Section: Pre-processing Dataset and Literature Reviewmentioning
confidence: 99%
“…For instance, the conversion to oil palm plantations has been identified as a driver of forest loss both outside and within the boundaries of the Gunung Leuser National Park in Sumatra (Supriatna et al, 2017). Similarly, deforestation has occurred both outside and within the borders of Kalimantan's PAs (Krasovskii et al, 2018). These too are threatened by illegal logging and oil palm expansion (Nellemann, 2007).…”
Section: Effects Of Anthropogenic Pressuresmentioning
confidence: 99%
“…We calculated OA, PA and UA in each disturbance detection (i.e., only with Sentinel-1, only with Landsat 8 and combining Landsat 8 and Sentinel-1). We treated disturbances detected before the actual disturbance date as commission errors of disturbance, in accordance with other studies (e.g., References [20,21,35]). However, disturbances detected within 10 days before the actual date were regarded as correct detections, because the visual interpretation had an uncertainty of 9.1 days (the weighted average interval of available PlanetScope and RapidEye images used in the visual interpretation).…”
Section: Validationmentioning
confidence: 99%
“…Dense time series satellite data can provide more detailed information than bi-temporal or annual satellite data [19][20][21][22]. The use of temporally dense satellite data to detect forest disturbances is particularly suitable in the tropics, because rapid vegetation recovery can obscure the signs of disturbance events [23,24].…”
Section: Introductionmentioning
confidence: 99%